Increasing Students' Understanding of Healthy Lifestyles in Efforts to Prevent Diarrhea in Elementary Schools - Adnan, Yudi; Muftaga, Nur Faiqah Firda; Khayani, Nur Annisa; Rahman, Zaskia Maharani; Pratiwi, Indah Putri (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Diarrhea is still a public health problem in Indonesia, because of its high morbidity and mortality. There are 100,000 Indonesian children who die from diarrhea every year and 300 out of 1000 residents suffer from diarrhea throughout the year. An effective way to prevent diarrhea is to implement Clean and Healthy Living Behavior (PHBS). Therefore, it is important to provide community service to increase knowledge about hand washing behavior in school children. The aim of this service is to increase knowledge about PHBS for elementary school students by preventing diarrhea. The target is 33 students from SD Inpres Kanreapia, Balanlohe Hamlet, Kunciopao District. The service method uses a combination of providing materials with PowerPoint, educational songs, and hand washing practices. Extension evaluation uses pre-test and post-test questionnaires to measure knowledge and attitudes before and after extension, which are analyzed using the Wilcoxon test. The results of the activity showed that there was a very significant difference in knowledge before and after counseling. Counseling on good hand washing practices can influence the knowledge of grade 5 and 6 elementary school students who are respondents at SD Inpres Kanreapia in efforts to prevent diarrhea with clean and healthy living behavior.